2018
DOI: 10.1111/cei.13225
|View full text |Cite
|
Sign up to set email alerts
|

Th17 responses to pneumococcus in blood and adenoidal cells in children

Abstract: Summary Pneumococcal infections cause a large global health burden, and the search for serotype‐independent vaccines continues. Existing conjugate vaccines reduce nasopharyngeal colonization by target serotypes. Such mucosal effects of novel antigens may similarly be important. CD4+ Th17 cell‐dependent, antibody‐independent reductions in colonization and enhanced clearance have been described in mice. Here we describe the evaluation of T helper type 17 (Th17) cytokine responses to candidate pneumococcal protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…25,39 Using either live exposure to pneumococcus or immunization with WCV, we have previously shown that CD4 + Th17 responses to a number of antigens provide protection against colonization in mice 19 and can be detected in the peripheral blood mononuclear cells of human adults and children. [40][41][42] However, the nature and localization of these protective T m cells have not been previously examined.…”
Section: Discussionmentioning
confidence: 99%
“…25,39 Using either live exposure to pneumococcus or immunization with WCV, we have previously shown that CD4 + Th17 responses to a number of antigens provide protection against colonization in mice 19 and can be detected in the peripheral blood mononuclear cells of human adults and children. [40][41][42] However, the nature and localization of these protective T m cells have not been previously examined.…”
Section: Discussionmentioning
confidence: 99%
“…This study elucidates the possible mechanisms associated with OME and pneumococcal carriage. Future novel therapeutics capable of modifying the balance of Th17/T reg function or direct targeting the IL-17A related inflammatory response might be beneficial for children with persistent OME or recurrent AOM requiring repeated ventilation tube insertion 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that CD4+ T helper type 17 (Th17) cell response leads to the reduction of pneumococcal colonization, killing and clearing of pneumococci by recruiting neutrophils to the site of infection. This type of response could reduce pneumococcal colonization, promoting clearance and is independent of CPS type [ 53 , 54 , 55 , 56 , 57 ].…”
Section: Emerging Methodsmentioning
confidence: 99%